2007
DOI: 10.1007/s11240-007-9324-2
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated genetic transformation of grapevine (Vitis vinifera L.) with a novel stilbene synthase gene from Chinese wild Vitis pseudoreticulata

Abstract: A novel stilbene synthase gene (STS), cloned from Chinese wild Vitis pseudoreticulata (W. T. Wang) and responsible for synthesis of the phytoalexin resveratrol in grapevine, was successfully transferred into V. vinifera L. cv. Thompson Seedless via Agrobacterium tumefaciens-mediated transformation. Using transformation procedures developed in the present study, 72% GFP-positive germinated embryos were produced with about 38% of transformed embryos regenerated into normal plantlets. Integration of the STS gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…Some of these compounds also possess promising therapeutic activity in various cancers, including breast, prostate, and neuroblastoma (Aggarwal et al 2004;Laux and Aregullin 2004;King et al 2005;Baur and Sinclair 2006). Direct evidence of resveratrol's biological activity (Adrian et al 1997) and a clear relationship between its production and disease resistance have been demonstrated using transgenic tobacco (Hain et al 1993), oil-seed (Thomzik 1993), tomato Giovinazzo et al 2005;Nicoletti et al 2007), rice (Stark-Lorenzen et al 1997), wheat (Leckband and Lörz 1998), kiwi (Kobayashi et al 2000), alfalfa (Hipskind and Paiva 2000), apple (Szankowski et al 2003), papaya (Zhu et al 2004), banana (Vishnevetsky et al 2005), pea (Richter et al 2006), hop (Schwekendiek et al 2007) and grapevine (Fan et al 2008). On the other hand, little is known about cis-acting elements and transcription factors controlling expression of stilbene synthase in response to various environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these compounds also possess promising therapeutic activity in various cancers, including breast, prostate, and neuroblastoma (Aggarwal et al 2004;Laux and Aregullin 2004;King et al 2005;Baur and Sinclair 2006). Direct evidence of resveratrol's biological activity (Adrian et al 1997) and a clear relationship between its production and disease resistance have been demonstrated using transgenic tobacco (Hain et al 1993), oil-seed (Thomzik 1993), tomato Giovinazzo et al 2005;Nicoletti et al 2007), rice (Stark-Lorenzen et al 1997), wheat (Leckband and Lörz 1998), kiwi (Kobayashi et al 2000), alfalfa (Hipskind and Paiva 2000), apple (Szankowski et al 2003), papaya (Zhu et al 2004), banana (Vishnevetsky et al 2005), pea (Richter et al 2006), hop (Schwekendiek et al 2007) and grapevine (Fan et al 2008). On the other hand, little is known about cis-acting elements and transcription factors controlling expression of stilbene synthase in response to various environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…VpSTS-overexpressing V. vinifera cv. Thompson seedless, under control of the highly active cauliXower mosaic virus 35S promoter were shown to have a resveratrol concentration 5.5 times higher than that of non-transformed control plants (Fan et al 2008). This prompted us to investigate the novel regulatory mechanism of STS in Chinese wild Vitis.…”
Section: Introductionmentioning
confidence: 99%
“…To construct the expression vector of VpROMT, the expression vector pWR306 derived from pCAMBIA1303 and pSB166 as previously described by Fan et al (2008) was used. The VpROMT gene cloned from V. pseudoreticulata driven by enhanced cauliflower mosaic virus 35S promoter (ED35S) fused after a 5′-untranslated leader sequence from tobacco mosaic virus Omega (designated as ED35S/X) was inserted into pWR306.…”
Section: Construction Of Pvpromt::gus Fusion Vectormentioning
confidence: 99%
“…We previously reported the gene encoding STS in transgenic Thompson seedless (Fan et al 2008) and recently characterized the novel STS promoter from the highly powdery mildew (PM)-resistant Chinese wild Vitis pseudoreticulata (Xu et al 2010). Here, we isolated the VpROMT gene from Chinese wild V. pseudoreticulata, which had 98.9% and 98.3% identity to the resveratrol O-methyltransferase gene of V. vinifera at the nucleotide and amino acid levels.…”
Section: Introductionmentioning
confidence: 99%
“…Stilbene synthase (STS) or resveratrol synthase condenses three molecules of malonylCoA and one molecule of cumaryl-CoA to form t-resveratrol (Rupprich et al 1980;Xu et al 2010). STS exists as a multigene family in most stilbenoid-producing species, including grapes, peanuts, and pines (Sparvoli et al 1994;Fan et al 2008;Chong et al 2009). Southern blot experiments have suggested that the genome of Vitis vinifera contains 15-20 STS genes (Sparvoli et al 1994).…”
Section: Introductionmentioning
confidence: 99%